APPLICATION OF AUDIO LINGUAL METHOD IN TEACHING OF SPEAKING - Babaxanova Dildoraxon Ikromjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article shows the importance of the audio lingual and authentic materials in teaching speaking, which is very interesting subject for the language teaching teachers. For most people, the ability to speak a foreign language is synonymous with knowing that language because speech is for them the basic means of human communication. Language learners no longer expect the traditional approach of their teachers based on developing mainly the grammatical competence and using methodology popular in the past.